(untitled) (Research, Society and Development, 2022)
Ultrasound has relatively low use in the veterinary practice of cattle, especially in the diagnosis of respiratory diseases. There is little information on imaging patterns and occurrence of these diseases in calves from dystocic parturition, especially in the ability to diagnose the subclinical respiratory diseases. The correct clinical diagnosis aims to support efficient growth and expression of genetic potential for the replacer calves. Eighteen Holstein calves, five of which did not require assistance during birth and thirteen calves from dystocic parturition had the respiratory system evaluated by ultrasound. The objective was to describe and compare the pulmonary ultrasound aspects of calves from dystocic parturitions, compared to calves born without any aid. The degree of dystocia was classified on a scale from 1 to 5 points and the categorization of ultrasound images considered the presence or absence of pulmonary lesions. The ultrasound examination was able to diagnose animals affected with BRD in a subclinical manifestation, considering that none of the animals that presented pulmonary consolidation showed clinical signs of respiratory diseases. All cows with dystocia were classified as grade 2 dystocic parturition. There was no correlation between normal delivery (grade 1) and mild dystocia (grade 2) and occurrence of pulmonary consolidation.